Architectural Narratives: Exploring Anandi by Ghulam Abbas within the nexus of Place Theory, Social Logic of Space and Phenomenology - Iqbal, Saira (Annals of Human and Social Sciences, 2024)
The research aims to analyze the emotional and psychological dimensions of place attachment, emphasizing the symbolic significance of architecture in shaping communal identities. It investigates how built environments influence human experiences and advocates for inclusive urban development to address social inequalities. Ultimately, this paper seeks to enrich architectural discourse by highlighting the transformative potential of marginalized communities within the framework of inclusive urban spaces. The relationship between architecture and society profoundly shapes human experiences and identities. In Ghulam Abbas’s Anandi, the architectural settings significantly impact the lives of marginalized communities, particularly the "Zanan-e-bazaari" (women of the marketplace). However, their perspectives are often overlooked in urban and architectural discussions. This study addresses this gap by exploring how architectural environments affect these communities through interdisciplinary frameworks like Place Theory and Phenomenology. By examining the emotional aspects of place attachment, the research aims to illuminate the symbolic role of architecture in reflecting societal values and to advocate for inclusive urban development that amplifies marginalized voices. Utilizing a qualitative, interdisciplinary methodology, this study analyzes Anandi, integrating insights from architectural theory, sociology, and cultural geography. Operating within the frameworks of Place Theory, Social Logic of Space, and Phenomenology allows for a comprehensive analysis of the text. Abbas’s narrative reveals the symbolic role of architecture in reflecting societal values and behaviors. The vibrant marketplace serves as a microcosm of social norms and biases, shaping identities and influencing interactions. Future research in architectural humanities should delve into the narratives embedded within built environments, emphasizing their role in shaping cultural identities and fostering more inclusive spaces